Analisis Industri Rumah Tangga Kerupuk Ikan dan Kontribusinya Terhadap Pendapatan Keluarga di Kelurahan Jelmu Kota Jambi - Wiyan Mailindra; Muhammad Amali (J-MAS (Jurnal Manajemen dan Sains), 2019)
The aim of this study is the first to know the characteristics of industrial workers' households in the village of fish crackers jelmu jambi city views from sex, age, education level, the number of dependents, employment status, duration of operations and the initial capital. Secondly to study and analyze the amount of household income of industrial workers in the village of fish crackers jelmu jambi city. Third to know how much revenue contribution of household industry workers fish crackers on family income in Sub Jelmu. From the discussion we know that the characteristics of the respondents viewed the sex, most craftsmen female fish crackers or equal to 80 percent of 15 respondents. Then in terms of age craftsmen fish crackers between 40-49 years of age or 46.67 percent of the 15 people total respondents. Viewed from the level of education in the village of fish crackers pengarjin jelmu most educated junior or 46.67 percent. Number of dependents of each of the respondents ranged between 1-6 people. Among 10 respondents, or 66.67 per cent with two-3orang family members only. From satatus jobs, most of the respondents made this fish crackers craft business as a major work that is equal to 73.33 percent. Old businesses ranging from 10-30 years. Judging from the initial capital issued by the craftsmen of fish crackers ranging from Rp. 350,000 – 699,000 totaling 10 respondents or 66.67 percent of total respondents. Of the total employment of each worker is different, ranging from 1-4 people. In terms of revenue ranging from Rp. 1,500,000 – 2,000,000.- per month. Acceptance is not reduced sales of capital and production costs. Then the family income of the highest fish crackers craftsmen USD 1.225 million per month. And lowest income of Rp. 665,000.- per month. Meanwhile, cracker craftsmen revenue contribution of fish to the family income amounted to 71.72 percent. With average family income of ± Rp. 926,266.67.- per month. And the average income of farmers amounted to ± Rp fish crackers. 630,266.67.- per month.